2019
DOI: 10.1039/c9cp00737g
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical approach to the role of different types of electrons in planar elongated boron clusters

Abstract: While the stability of planar elongated pure boron clusters is determined by their […σ2(n+1) π12(n+1) π22n] electronic configuration, the rectangle model can rationalize the π electronic configuration of rectangle-shaped structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…Since it was first proposed to rationalize the apparent stability of cyclopropane, the concept of σ-aromaticity has been used to explain the bonding in a wide variety of chemical systems. It has been particularly valuable to understand the bonding and stability of the all-metal aromatic and antiaromatic systems and boron clusters. Gold clusters have received tremendous attention over the past 2 decades, because of the discovery of catalytic effects by gold nanoparticles. , One of the most surprising findings is that negatively charged gold clusters (Au n – ) can be planar up to Au 12 – . The planarity has been generally understood to be due to the strong relativistic effects that can induce 6s–5d hybridization. The Au 6 – cluster was in fact first proposed to be a D 6 h ring based on the observation of a single vibrational progression in photodetachment spectroscopy . A subsequent theoretical calculation found that the global minimum of Au 6 – was a triangle with D 3 h symmetry, which was confirmed by joint experimental and theoretical investigations. ,…”
Section: Introductionmentioning
confidence: 99%
“…Since it was first proposed to rationalize the apparent stability of cyclopropane, the concept of σ-aromaticity has been used to explain the bonding in a wide variety of chemical systems. It has been particularly valuable to understand the bonding and stability of the all-metal aromatic and antiaromatic systems and boron clusters. Gold clusters have received tremendous attention over the past 2 decades, because of the discovery of catalytic effects by gold nanoparticles. , One of the most surprising findings is that negatively charged gold clusters (Au n – ) can be planar up to Au 12 – . The planarity has been generally understood to be due to the strong relativistic effects that can induce 6s–5d hybridization. The Au 6 – cluster was in fact first proposed to be a D 6 h ring based on the observation of a single vibrational progression in photodetachment spectroscopy . A subsequent theoretical calculation found that the global minimum of Au 6 – was a triangle with D 3 h symmetry, which was confirmed by joint experimental and theoretical investigations. ,…”
Section: Introductionmentioning
confidence: 99%
“…This B cluster, experimentally and theoretically characterized, is considered a naphthalene analogue due to its 10 π-electrons. 182,183…”
Section: Introductionmentioning
confidence: 99%
“…Although many experimental and theoretical studies have been reported investigating different aspects of boron clusters, 22–31 much less has been done on the electron correlation effects. Theoretically, it is a very difficult task to obtain accurate electron-correlation energies of these clusters, e.g.…”
Section: Introductionmentioning
confidence: 99%